1992
DOI: 10.1021/j100182a084
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies on zeolites. 6. Temperature dependence of diffusion of methane in silicalite

Abstract: 30)K = exp Accepting that yc = ya i.e., Ay = 0 and n, = ns, we deduce that or Mazer et report an aggregation number of 10 for the formation of a primary micelle, Le., n, = 10. Accepting our Awo values and AGO = -RT In K, it is deduced that AGO varies in the range -1.3 to -6.7 kcal/mol. Although several simplifications are involved, such values are very close to those obtained by Mazer et al. (from -3.8 to -6.7 depending on experimental conditions) for the above-mentioned bile salts. Giglio et al." have demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 4 publications
9
112
2
Order By: Relevance
“…There seems to be some indication that framework vibrations can alter the diffusivities of tightly fitting molecules, 56,57 even though this appears not to be the case for the diffusion of small alkanes through cation-free sieves. 58,59 We stress that to compare a flexible framework with a rigid framework the flexibility should be modeled in such a way that the two structures are on average identical. This implies that the reference bond lengths should be taken from the rigid structure.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be some indication that framework vibrations can alter the diffusivities of tightly fitting molecules, 56,57 even though this appears not to be the case for the diffusion of small alkanes through cation-free sieves. 58,59 We stress that to compare a flexible framework with a rigid framework the flexibility should be modeled in such a way that the two structures are on average identical. This implies that the reference bond lengths should be taken from the rigid structure.…”
Section: Discussionmentioning
confidence: 99%
“…, which, in previous simulations, 4 provided an adequate description of methane-silicalite interaction, and are consequently fairly suitable for describing ͑CH 3 ͒-O interactions.…”
mentioning
confidence: 86%
“…Simulations with a vibrating lattice showed that the framework can act as an effective ''heat bath'' for the sorbates; at any time their velocities are thermalized to a Boltzmann distribution through a continuous energy exchange with the lattice atoms. 4 This fact can have some effects on the diffusion and other properties of the guest species; until now MD studies on this topic have mainly concerned with adsorbed Lennard-Jones ͑LJ͒ spheres, representing methane or xenon. [4][5][6][7][8][9] The effects of framework vibrations should be greater on nonspherical sorbates larger than methane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…90 The crossing of the lines gives the parameters for which both the Henry coefficient and heat of adsorption agree with the experimental results. For comparison, the stars are the parameters of the model proposed by Bezus et al, 74 Goodbody et al, 91 Hufton et al, 92 and Demontis et al 93,74,[91][92][93] The triangle gives the model of Dubbeldam et al 94 Pascual and co-workers 95,96 used an approach that relies less on the availability of accurate experimental data. This method relies on the assumption that alkane-zeolite interactions can be estimated from the Lorentz-Berthelot mixing rules for the anisotropic united-atom model:…”
Section: Zeolite-adsorbate Interactionsmentioning
confidence: 99%